Formulasi Bioinsectisida Dari Bakteri Bacillus Thuringiensis - Emmy Ratnawati; Rahyani Ermawati; Rahayu Susilowati (Balai Besar Kimia dan Kemasan, 1996)
Among the pathogenic bacteria, Bacillus Thuringiensis is the one of potential bacterial insecticides which has the capability in crystallizing protein in the cell as an entomoxcyn or active agent of bioinsecticides. The advantages of bioinsecticides usage are toxic only to the insect target, and it is net creating bioinsecticides are toxic. The commercial form of Bacillus Thuringiensis is made from the active bacteria agent as mixing of spora and protein crystal and carrier. The active bacteria agent prepared by two kinds of fermentation methods, sub merged fermentation and semi solid fermentation. There are 7 bioinsecticide form available in Indonesia such as Granule, Flowable Concentrate, Wettable Powder, Suspension, Aqueous Suspension, Water Dispersible Granule and Ultra Low Volume. There product are not produce yet in Indonesia, just repacking for commercial purposes.